The impact of skin-to-skin contact upon stress in preterm infants in a neonatal intensive care unit - Pavlyshyn, Halyna; Sarapuk, Iryna; Saturska, Uliana (Frontiers in Pediatrics, 2024)
Neonatal stress significantly affects the early adaptation, maturation and longterm development of preterm infants.The objective of the study. To investigate the effect of skin-to-skin contact (SSC) on stress level in preterm infants.The research was a prospective study. Stress indicators (cortisol, melatonin) were measured before the SSC began (pre-intervention level) and after this intervention (post-intervention).Results. The study included 150 preterm infants in the NICU with gestational age (GA) ≤ 36 weeks. Pre-intervention salivary cortisol level was higher in extremely and very preterm neonates compared to moderate and late preterm newborns (p=0.028), in children with low Apgar scores (p=0.041), in those who were on mechanical ventilation (p=0.005), and suffered neonatal sepsis (p=0.005). Pre-intervention melatonin level was lower in children with low Apgar scores (p=0.032).Salivary cortisol levels were significantly decreased after SSC in preterm infants (preintervention: 0.294 [0.111; 0.854] μg/dL vs. post-intervention: 0.127 [0.070; 0.229] μg/dL, p<0.001), and urinary melatonin levels were significantly increased after SSC (pre-intervention: 4.01 [2.48; 6.34] ng/mL vs. post-intervention: 5.48 [3.39; 9.17] ng/mL, p<0.001). A greater reduction in cortisol levels after skin-to-skin contact was revealed in infants with a lower gestational age (p=0.022), in boys compared to girls (p=0.012), in infants with respiratory distress syndrome (p=0.048), in those who had mechanical ventilation compared to non-ventilated neonates (p=0.008), and in infants with seizures (p=0.036). The melatonin levels increased more intensively in infants with low Apgar scores (p=0.002), and in those with late-onset sepsis (p=0.006).The reduction in cortisol levels and the increase in melatonin levels provided strong evidence that SSC ameliorated the NICU-related stress in preterm infants. We found higher indicators of stress and more dramatic responses to SSC in reducing indicators of stress in infants with lower GA than in infants with higher GA, indicating that SSC may be even more important for lower GA infants. The infants who need SSC the most should not be denied the care they need to reduce the stress they experience from being born too soon and continuing their gestational development in the stressful environment of the NICU.